Asuhan Keperawatan Gerontik Pada NY. W Dengan Pemberian Rebusan Daun Cincau Hijau Untuk Menurunkan Tekanan Darah Di Wilayah Kerja Puskemas Sei. PancurKota Batam Tahun 2021 - Dedy Siska (CV. ADIBA AISHA AMIRA, 2021)
Hypertension is the number 1 cause of death in the world and Hypertension is the third largest cause of death in Indonesia with a percentage of 6.7% after stroke and heart disease (Ministry of Health RI, 2019). shows that the highest prevalence of hypertension is in Batam, amounting to 4,587 people (Riskesdas Kepri, 2018). Based on data from the Health Office in 2019, the highest prevalence of the disease in Batam was Hypertension with a total of 70,122 people (Batam City Health Office 2019). This professional scientific paper aims to perform Gerontic Nursing Care for Mrs.W By Giving Cyclea Berbata Miers Leaf Decoction To Lower Blood Pressure At Sei.Pancur Health Center Batam City In 2021, and held on July 21, 2021 to July 30, 2021. The method used in this Professional Scientific Writing paper is a case study conducted based on the stages of nursing care. Includes assessment, diagnosis, intervention, implementation and evaluation of nursing. The results of professional scientific papers obtained 3 nursing diagnoses, namely the risk of decreased cardiac output associated with increased afterload, headache associated with increased cerebral vesicular pressure, and sleep disruption associated with discomfort (pain). Through the therapy of cyclea berbata miers leaf decoction out on Mrs.W for 5 days of administration, the blood pressure results were obtained before doing 170/100mmHg and after 5 days of administration it became 130/90mmHg. Through the cyclea berbata miers leaf decoction therapy, it is hoped that it can become one of the non-pharmacological treatments to reduce blood pressure in hypertensive patients